Outcomes and Complications of Tibiotalocalcaneal Arthrodesis - Aly M. Fayed MD, MSc; Nacime Salomao Barbachan Mansur MD, PhD; Natalie Glass PhD; Phinit Phisitkul MD; John Femino MD (Foot & Ankle Orthopaedics, 2023)
Category: Ankle Arthritis; Hindfoot Introduction/Purpose: Tibio-talo-calcaneal (TTC) arthrodesis is usually a salvage procedure to address several hindfoot and ankle conditions. Non-union rate after TTC fusion is variably reported 3.4% - 48%. The aims of this study were to describe the outcomes and complications of this procedure and to determine potential risk factors associated with non-union. Methods: In this IRB-approved retrospective cohort study, we used the following codes (28705,28725 and 27870) to search the medical records for all patients who underwent TTC fusion between 2006-2022. All relevant demographic data, surgical indications, surgery details (type of the graft, type of the implant, and surgical approach, associated procedures), post-operative course (complications and union rate) and follow-up duration were extracted. Descriptive statistics were performed, and continuous variables were described using median (interquartile range) and categorical variables were described using frequency (%) and mean (standard deviation, SD). Patients and surgery characteristics were compared between united and non-united cases using Wilcoxon Rank Sum Tests for continuous variables and Chi-squared or exact tests, as appropriate, for categorical variables. Analyses were performed using SAS statistical software version 9.4 (SAS Institute Inc., Cary, NC). Results: Fifty-one patients (53 feet) were included in the study. Long hindfoot fusion nails were used in 51 cases.Ten cases were routinely dynamized 8-10 weeks after surgery. In 24 (45.3%) patients, morselized allograft was combined with infuseTM and reamer irrigation aspiration autograft (RIA). In 20 (37.7%) patients, morselized allograft was combined with infuseTM only. There were 6 non-union cases (11.3%). When comparing patients and surgery characteristics between non-union versus union group, smoking (P = 0.0150) and routine dynamization (P= 0.0297) were higher in the non-union group. No difference in union rates between different types of graft. Frequency of other complications is listed in (Figure 1). Follow up duration was 27.2 months (range 4-108 months). Conclusion: TTC fusion achieves good union rate (88.68%), however it carries a relatively high risk of complications. Routine dynamization of the TTC nail at 8-10 weeks could be a risk factor for non-union. Smoking was also associated with a high non- union rate.